Enhancement of the edible quality and shelf life of soft‐boiled chicken using MAP. Issue 3 (18th February 2020) - Deng, Shaolin; Li, Ming; Wang, Huhu; Xu, Xinglian; Zhou, Guanghong
Abstract: In order to commercialize soft‐boiled chicken, a traditional Asian food, this work was performed to evaluate the effect of the packages on the edible quality. Soft‐boiled chickens were packaged with air packaging (AP) or modified atmosphere packaging (MAP, MN:100% N2 and MC:30%CO2 /70%N2 ) conditions. Total viable counts reached the acceptable limit of 4.90 Log CFU/g at 1.5, 2.5, and 4 days of storage under AP, MN, and MC, respectively. However, sensory acceptance limits, based on overall acceptance by the professional panelists, were not reached until one day later. The TVB‐N content of MAP was lower than that of the AP. The finding indicated that the shelf life of soft‐boiled chicken could be extended by two days using MAP with CO2 . These findings will provide basic reference for the packaging of cooked meat and also provide information on poultry processing techniques that could be applied at commercial scales. Abstract : According to our microbiology determination and sensory evaluation results, MAP treatment with 30% CO2 /70% N2 can prolong the shelf life of SC to 4 days.